Recent Developments in Higher Education in Singapore - Tan, Jason (International Higher Education, 1999)
Amid the recent economic turmoil in East and South east Asia, the Singapore government continues to press ahead with its plans to review the higher education system. The primary motivation for doing so is the maintenance of national economic competitiveness in the global economy. These changes in higher education are being undertaken in tandem with reforms in the primary and secondary sectors of education.